A Conceptual Model of Ethical Leadership in Ulil Albab-Oriented Islamic Higher Education - Nurmala Octavian Arindi (PT. Banjarese Pacific Indonesia, 2026)
Purpose: This article develops and sharpens an Ulil Albab-oriented ethical leadership framework for Islamic higher education, with particular relevance to business and economics programmes that are expected to integrate professional competence, moral reasoning, spiritual accountability, and public responsibility. Design/methodology/approach: The study uses an integrative literature review to synthesize seminal and recent scholarship on ethical leadership, Islamic work ethics, spiritual leadership, moral identity, institutional ethics climate, and Ulil Albab education. The analysis is organized around four conceptual categories: moral person, moral manager, Islamic virtue-based leadership, and institutional ethics climate. Findings: The review indicates that ethical leadership in Islamic higher education cannot be reduced to compliance, charisma, administrative control, or symbolic religiosity. It becomes educationally transformative when leaders embody amanah, justice, consultation, truthfulness, benevolence, and maslahah while institutionalizing these values through transparent assessment, academic integrity systems, service learning, reflective pedagogy, and quality assurance. The proposed model positions Ulil Albab ethical identity, expressed through dhikr, fikr, and amal, as a mediating mechanism between Islamic ethical leadership and student/institutional ethical outcomes. Institutional ethics climate strengthens this relationship by converting values into daily academic routines. Originality/value: The article contributes a theoretically grounded and testable model that links modern ethical leadership theory with Islamic educational anthropology. It offers propositions, operational indicators, and empirical research directions for future studies in Islamic business and economics education.